Socio-Spatial Differentiation of Chinese Shadow Education Activities During its Peak Period: A Case Study of Dalian Urban Area - Tianbao, Liu; Zhenbo, Pan (Education and urban society, 2025)
Based on the survey data of shadow education activities of junior middle school students in Dalian, China in 2020, this paper analyzes the socio-spatial differentiation of participation, activity spatial distribution and travel distance. It’s found that: (1) The participation rate reaches 74.17%. In general, the higher socioeconomic status strata have more advantages both in participation rate and registered subjects’ number. Spatially, though the suburban area has the lowest participation rate, the largest registered subjects’ number per student is there. (2) Spatial agglomeration of shadow education activities is obvious, mainly gathering in commercial centers, around schools and residential areas and forming a relatively dispersed multi-core structure. The activities of the middle socioeconomic status strata are most widely distributed. (3) The average travel distance of shadow education is almost twice that of travel to school. The average distance goes up with the rise of social strata with the only exception of the highest stratum because of their enjoying of superior locations. Students in the suburban area have the longest travel distance due to their large number of travels to the urban core area. Also, students registered for more than one shadow education subjects’ number have a much higher proportion of long-distance travel.